The Principal’s Role in Implementing Differentiated Instruction in Vocational High Schools: A Case Study of SMK N 2 Depok, Sleman, Yogyakarta, Indonesia - Basyir, Akmal (Universitas Muhammadiyah Yogyakarta, 2026)
Differentiated instruction is a pedagogical approach that adapts to students' diverse potential, interests, and needs. The role of the principal in shaping and implementing policies within a school is crucial, particularly in the application of differentiated instruction at SMK N 2 Depok, Sleman, Yogyakarta. This study aims to describe the principal's leadership role in facilitating differentiated instruction at the school. This research employed a descriptive, qualitative methodology in which the researcher engaged directly with the principal and teaching staff. Data collection was conducted through interviews and document analysis, and data validity was assessed through triangulation. The data were then analyzed through data reduction, data presentation, and conclusion drawing. The findings indicated that differentiated instruction has been implemented at SMK N 2 Depok, particularly in process differentiation. However, the lesson-planning documents lack explicit guidelines for implementing differentiated instruction. While the principal has played a significant role in leading the process, there is room to expand this role. The principal has actively employed both instructive and humanistic approaches in leadership. However, the evaluation process, conducted by the principal and an assessment team, is time-consuming, resulting in delays in addressing inconsistencies in teaching practices. Additionally, the evaluation remains broad and does not specifically assess the implementation of differentiated instruction. Nonetheless, the evaluations have prompted positive changes in teaching patterns, and further enhancements are necessary to optimize student support and facilitate effective learning.